Fresh Insights Into SLC25A26: Potential New Therapeutic Target for Cancers: A Review - Xu, Yangheng; Hong, Zhisheng; Yu, Sheng; Huang, Ronghan; Li, Kunqi; Li, Ming; Xie, Sisi; Zhu, Lvyun (Oncology Reviews, 2024)
SLC25A26 is the only known human mitochondrial S-adenosylmethionine carrier encoding gene. Recent studies have shown that SLC25A26 is abnormally expressed in some cancers, such as cervical cancer, low-grade glioma, non-small cell lung cancer, and liver cancer, which suggests SLC25A26 can affect the occurrence and development of some cancers. This article in brief briefly reviewed mitochondrial S-adenosylmethionine carrier in different species and its encoding gene, focused on the association of SLC25A26 aberrant expression and some cancers as well as potential mechanisms, summarized its potential for cancer prognosis, and characteristics of mitochondrial diseases caused by SLC25A26 mutation. Finally, we provide a brief expectation that needs to be further investigated. We speculate that SLC25A26 will be a potential new therapeutic target for some cancers.